Peningkatan Keterampilan Menulis Teks Deskripsi Melalui Teknik Show, Don't Tell Pada Siswa Kelas V Sd Negeri 1 Temuwangi Pedan Klaten Tahun Pelajaran 2025/2026 - Kasmi .; Dwi Bambang; Triyono .; Hersulastuti . (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Writing is an important language skill and relatively difficult for elementary school students to master, particularly writing descriptive texts. A pre-survey conducted in fifth-grade students at SD Negeri 1 Temuwangi Pedan, Klaten, found that students' descriptive writing skills were still low, as indicated by low learning motivation, suboptimal student engagement, and learning outcomes often falling below the Minimum Completion Criteria (KKM). One contributing factor is the use of conventional and less varied learning methods. Therefore, innovative learning methods are needed to encourage students to be active and creative in writing, one of which is the Show, Don't Tell technique. This study aims to improve descriptive writing skills through the application of the Show, Don't Tell technique in fifth-grade students at SD Negeri 1 Temuwangi Pedan, Klaten, in the 2025/2026 academic year. This study, a Classroom Action Research (CAR), was conducted in two cycles using the Suharsimi Arikunto model, encompassing planning, implementation, observation, and reflection. The study subjects were 18 students. Data collection techniques used observation, tests, questionnaires, and documentation. Data analysis was carried out quantitatively and qualitatively. The results of the study showed an increase in students' descriptive text writing skills. In cycle I, learning completeness reached 77.78%, then increased in cycle II to 83.33%. In addition, the questionnaire results showed that students' responses to the application of the Show, Don't Tell technique were in the positive category. Thus, it can be concluded that the application of the Show, Don't Tell technique is effective in improving the descriptive text writing skills of fifth-grade students of SD Negeri 1 Temuwangi Pedan Klaten.